Evaluation of Pregnant Knowledge and Adherence Regarding Supplemental Iron, Folic acid, Calcium, and Vitamins During Pregnancy - Karim, Walaa A.; Rabea, Ihsan S.; Abdulwahid, Hameeda H. (Journal of Contemporary Medical Sciences, 2024)
Objectives: The aim of the present study is to evaluate the knowledge as well as the rate of adherence to supplement medications. Methods: The cross-sectional study was carried out at a teaching hospital for obstetrics and gynecology in Karbala with 100 pregnant women at the second trimester, data were collected using two questionnaires, one about knowledge and other about adherence to micronutrient supplementation, laboratory tests were used to determine the levels of Hemoglobin and plasma level of calcium, and vitamin D. Results: the overall adherence rate to supplement medication among pregnant women was low in spite of good knowledge score. Biochemical laboratory results showed more than half of participants were found to have haemoglobin Less than normal level. Most of participant confirmed to have deficiency of plasma 25-Hydroxy-vitaminD, and more than two third of them have normal calcium level. Conclusion: the present study revealed that most pregnant women have a poor adherence to micronutrient supplementation, therefore there is a need for interventional strategies to optimize adherence.